Front Cover: Process Monitoring of Lactone Ring Formation and Opening by Operando Attenuated Total Reflectance Infrared Spectroscopy (Chem. Methods 10/2025) - Bos, Jelle W.; de Peinder, Peter; Janssens, Joris C. L.; Oord, Ramon; Monai, Matteo; Vogt, Eelco T. C.; Weckhuysen, Bert M. (Chemistry methods, 2025)
The Front Cover features a liquid‐phase hydrogenation reactor, employing attenuated total reflectance‐infrared (ATR‐IR), Raman, and fluorescence spectroscopy under industrially relevant conditions. Specifically, it highlights the use of inline ATR‐IR spectroscopy and partial least‐squares regression to determine the concentrations of two bio‐derived lactones from the acquired spectra. In the Research Article by B. M. Weckhuysen and co‐workers (DOI: 10.1002/cmtd.202500054), the reactor design is clarified, and changes in the spectra not induced by concentration changes are pinpointed, shedding light on the challenges associated with performing spectroscopy under reaction conditions.